A Meta-Analysis of BRRI Conducted Ten Years Field Research on Transplanted Aman Rice in Bangladesh (Bangladesh Agronomy Journal, 2025)
In the cropping systems of Bangladesh, T. Aman rice has special significance. On the bright  side, the crop is grown utilizing monsoonal rain water. On the hind side, it faces natural hazards  such as early and terminal drought, and both early and late flooding. Therefore, variety choice  and  agronomic  management  are  the  key  considerations  for  a  successful  crop  harvest. Bangladesh Rice Research Institute (BRRI), the prime rice research institute of the country,  routinely  conducts  large  number  of  trials  across  the  country,  accounting  for  diverse environments, which include performance of varieties and management practices. This study  has compiled the body of this knowledge through meta-analysis to generate information using  10-year’s meta-data were gathered during the period of 2010 through to 2019. The average  yield in meta-data was 7.37 percent higher than national average of T. Aman rice yield of Bangladesh. Varieties under High Yield Potential (HYP) category averaged yield of 4.34 t ha)−1 and some newer varieties like BRRI dhan72, BRRI dhan79, BRRI dhan87, BRRI dhan76, BRRI dhan78, BRRI dhan80, BRRI dhan90 produced higher yield (above 4.5 t ha). Again,−1 many old varieties such as BR 3, BR 4, BR 10, BR 11, BRRI dhan31, BRRI dhan32 produce  yield close to 4.5 t ha. This study did not find a consistent pattern of response of the three −1measured management components – transplanting time, seedling age and seedling density. Environmental response on the yield of rice varieties varies between years and locations of the experimentations (environments), indicating environment played a prominent role on yield. Eventually, this study is enough to create the thirst of researchers in the rice research field here  some further feasibility of rice yield improvement would emerge from the study of meta-analysis.  The results provide a clear message to stakeholders that variety-environment-management synchronized approach is essential for improved yields of T. Aman rice in Bangladesh.Bangladesh Agron. J. 2025, 28(1): 66-88